Mandibular canine-lateral incisor and maxillary bilateral canine-premolar transposition: Report of two cases - Deepa Dhruvakumar; Vidhi Munjal; Saras Mediratta (Wolters Kluwer Medknow Publications, 2014)
Tooth transposition is a rare developmental anomaly in which the adjacent teeth switch/swap their positions and may create problems both esthetically and functionally. The maxillary permanent canine is the tooth most frequently involved, which is often transposed with the first premolar followed by transposition between the maxillary permanent canine and maxillary lateral incisor. This paper reports two cases of tooth transposition, one in mandibular arch involving the right lateral incisor and canine; and the other bilateral transposition in maxillary arch involving the first premolars and canine. It also focuses on the etiology and the prevalence of this interesting phenomenon called transposition.